The philosophy of social science an introduction - Hollis, Martin 1938-1998 (Cambridge University Press, 1994)
This textbook by Martin Hollis offers an exceptionally clear and concise introduction to the philosophy of social science. It examines questions which give rise to fundamental philosophical issues. Are social structures better conceived of as systems of laws and forces, or as webs of meanings and practices? Is social action better viewed as rational behaviour, or as self-expression? By exploring such questions, the reader is led to reflect upon the nature of scientific method in social science. Is the aim to explain the social world after a manner worked out for the natural world, or to understand the social world from within?
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Philosophie; Sozialwissenschaften; Social sciences / Philosophy; Theorie; Soziales Handeln; Einführung; Lehrbuch